Knowledge and Attitude of Nursing Staff on Baby-friendly Hospital Initiative Practices in a Tertiary Hospital - Mathema, Smriti; Shrestha, Sabina (Journal of Kathmandu Medical College, 2020)
Background: Within a hospital setting, health professionals play a key role in providing the right information on breastfeeding and often this source are the nurses who have the primary opportunity to counsel, support and educate mothers on breastfeeding. The Baby Friendly Health Initiative (BFHI) has helped to motivate facilities providing maternity and newborn services worldwide to better support breastfeeding. Objective: The aim of this study is to help identify the knowledge gaps on the BFHI practices among nursing staff in a tertiary care center in Kathmandu. Methodology: A total of 27 nursing staff who encounter pregnant women admitted in the hospital up until post-delivery discharge were selected for the study. Data on knowledge of baby-friendly hospital initiative and attitude towards breastfeeding practices was collected using a structured interview between October and December 2019. Statistical analysis was done using SPSS version 20. Results: Only 41% were acquainted with the ten steps to successful breastfeeding of BFHI, out of whom more than half (55%) had a good level of knowledge. Majority of the participants showed a fairly correct attitude towards BFHI practices, except for the belief that there is no harm in introducing pre-lacteal feeds to babies. The opinion on demand feeding and the time of introduction of complementary feeding seemed to vary. Conclusion: There is an urgent need to re-evaluate the present knowledge of our nursing staff and to ensure they impart the right information. The only way to achieve this is through advocacy and training to promote, support and protect breastfeeding.